Exploring healthcare assistants' role and experience in pain assessment and management for people with advanced dementia towards the end of life: a qualitative study. Issue 1 (December 2017) - Jansen, Bannin; Brazil, Kevin; Passmore, Peter; Buchanan, Hilary; Maxwell, Doreen; McIlfatrick, Sonja; Morgan, Sharon; Watson, Max; Parsons, Carole
Abstract Background Pain assessment and management are key aspects in the care of people with dementia approaching the end of life but become challenging when patient self-report is impaired or unavailable. Best practice recommends the use of observational pain assessments for these patients; however, difficulties have been documented with health professionals' use of these tools in the absence of additional collateral patient knowledge. No studies have explored the role, perspectives and experiences of healthcare assistants in pain assessment and management in dementia; this study provides insight into this important area. Methods A qualitative approach was adopted, using key informant interviews with healthcare assistants caring for people with advanced dementia approaching the end of life in hospice, nursing home and acute care settings. Thematic analysis was the analytic approach taken to interpretation of interview data. Data were collected between June 2014 and September 2015. Results Fourteen participants took part in the study. Participants' average length of caring experience was 15.4 years and most were female. Three key themes emerged: recognising pain, reporting pain, and upskilling. Participants were often the first to notice obvious causes of pain and to detect changes in patient norms which signified hidden causes of pain. Comprehensive knowledge of resident norms enabled participants to observe for behavioural and nonverbal indicators of pain and distinguish these from non-pain related behaviours. Pain reporting was heavily impacted by relationships with professional staff and the extent to which participants felt valued in their role. Positive relationships resulted in comprehensive pain reports; negative relationships led to perfunctory or ambiguous reporting. Participants emphasised a desire for further training and upskilling, including in the use and reporting of basic pain tools. Conclusions Healthcare assistants are frontline staff who have a key role in direct patient care, spending a considerable amount of time with patients in comparison to other health professionals. These staff are often first to notice changes in patients that may signify pain and to alert professional staff. However, to ensure the quality of these reports, further efforts must be made in reversing stigma attached to this role and in upskilling these members of the healthcare team.